DAYA HIDUP DAN INTENSITAS SERANGAN BUBUK KAYU KERING HETEROBOSTRYCHUS AEQUALIS WAT PADA KAYU PULAI (ALSTONIA SCHOLARIS R.Br) - Ginuk Sumarni; Jasni Jasni (Jurnal Penelitian Hasil Hutan, 1988)
In  Indonesia  Heterobostrychus  aequalis  Wat is  a large size powder  post  beetle.  This species very commonly attacks highly  stachy  wood,  the  main  reason  why   they  are  used  in  this  experiment.In  this research pulai wood  (Alstonia  scholaris R.Br)  has been used for sample,  dried at temperature levels for 40°C, 60oC, 90oC, 100oC, 120oC, 150oC, 200oC and ambien air temperature.  On each side  of  wood  samples  ten  holes  were made  with  dimension  of 1,5 cm x 5 cm x 7 cm. Into  the hole larvaes of 1,5  month  old were placed.  The observations  were made  after  six  week  period.The result showed  that wood  dried on temperature  40°C could  reduce  the starch of about  9,08% so that  intensity of insect's  attack  were lower (score 44,2). High starch  content   was found  in the  wood  dried  at  temperature 200°C, that is 17,94%. In  this  sample  the  intensity   of  the  attack was higher,  that  scale  at  scoring.